Online Teaching: What do Teachers Think? - Chabra, Sonal; Chopra, Vanita (SCHOOL SCIENCE, 2020)
The teaching-learning process has been through a paradigm shift from face-to-face to online teaching using varied digital platforms in the current pandemic milieu. This transformation process was sudden and unscheduled and so has drawn attention towards the adaptation of the teaching community at large. The researchers aimed to explore the experiences of 100 school teachers towards online teaching. A self constructed questionnaire was used to ascertain the experiences and perceptions of teachers towards online teaching. Teachers’ responses brought to light that they are confident about online teaching and have adapted well to the situation. They highlighted the flexibility and reach to many learners as advantages of online teaching and challenges like connectivity issues and infrastructure.